2023
DOI: 10.1017/s0963180123000051
|View full text |Cite
|
Sign up to set email alerts
|

A Tale of Two Chimeras: Applying the Six Principles to Human Brain Organoid Xenotransplantation

Abstract: Cerebral organoid models in-of-themselves are considered as an alternative to research animal models. But their developmental and biological limitations currently inhibit the probability that organoids can fully replace animal models. Furthermore, these organoid limitations have, somewhat ironically, brought researchers back to the animal model via xenotransplantation, thus creating hybrids and chimeras. In addition to attempting to study and overcome cerebral organoid limitations, transplanting cerebral organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…This needs to be weighed against animal welfare and rights, and concerns related to the use of nonhuman primates they replace. A framework known as the Six Principles (6Ps) (Beauchamp and DeGrazia, 2020;DeGrazia and Beauchamp, 2021) aims to expand upon the 3Rs and be a practical means for assessing animal ethical issues like neural-chimeras and cerebral organoid xenotransplantation (Barnhart and Dierickx, 2023). In her 2021 thesis "Protecting In Vitro Human Brain Organoids: Why, When, and Which?, " Das (2021) delves into the ethical implications of using human brain organoids in research.…”
Section: Brain Organoids and Organoid Intelligence As The New Ethical...mentioning
confidence: 99%
“…This needs to be weighed against animal welfare and rights, and concerns related to the use of nonhuman primates they replace. A framework known as the Six Principles (6Ps) (Beauchamp and DeGrazia, 2020;DeGrazia and Beauchamp, 2021) aims to expand upon the 3Rs and be a practical means for assessing animal ethical issues like neural-chimeras and cerebral organoid xenotransplantation (Barnhart and Dierickx, 2023). In her 2021 thesis "Protecting In Vitro Human Brain Organoids: Why, When, and Which?, " Das (2021) delves into the ethical implications of using human brain organoids in research.…”
Section: Brain Organoids and Organoid Intelligence As The New Ethical...mentioning
confidence: 99%
“…Thus, if a broad neural network is necessary to realize consciousness, it is unlikely that conscious brain organoids would be created during the Generation stage. 7 That said, concerns regarding the creation of conscious organoids in vitro are not unrelated to transplantation. Consider the possibility that in vitro non-conscious brain organoids are transplanted into host animals and become conscious in vivo (9).…”
Section: Generationmentioning
confidence: 99%
“…For human brain organoid transplantation into animals, the welfare of the host animal must be given due consideration (both now and in the future). A recent study utilized the principles of animal ethics to analyze two cases of human brain organoid transplantation in animals and concluded that such transplantations would be morally inappropriate [7]. 16 It also pointed out that the behavior of chimeric animals has not been sufficiently examined to fully assess their welfare.…”
Section: Possible De-enhancement In Animalsmentioning
confidence: 99%
See 2 more Smart Citations